2022
DOI: 10.3390/w14142250
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemistry of Medium-Size Pristine Rivers in Boreal and Subarctic Zone: Disentangling Effect of Landscape Parameters across a Permafrost, Climate, and Vegetation Gradient

Abstract: We studied two medium size pristine rivers (Taz and Ket) of boreal and subarctic zone, western Siberia, for a better understanding of the environmental factors controlling major and trace element transport in riverine systems. Our main objective was to test the impact of climate and land cover parameters (permafrost, vegetation, water coverage, soil organic carbon, and lithology) on carbon, major and trace element concentration in the main stem and tributaries of each river separately and when considering them… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…They assert that large-scale, seasonally resolved transect studies of large riverine systems of Western Siberia are needed to assess the hydrochemical response of this environmentally important territory to ongoing climate change. An example of using such an approach for two contrasting rivers of the region-permafrost-affected Taz River and permafrost-free Ket River-is provided by Pokrovsky et al [8], who showed that climate warming in northern rivers may double or triple the concentration of DIC, Ca, Sr, U, but also increase the concentration of DOC, POC, and nutrients. The study applied a substituting-space-for-time approach for the south-north gradient of the studied river basins.…”
mentioning
confidence: 99%
“…They assert that large-scale, seasonally resolved transect studies of large riverine systems of Western Siberia are needed to assess the hydrochemical response of this environmentally important territory to ongoing climate change. An example of using such an approach for two contrasting rivers of the region-permafrost-affected Taz River and permafrost-free Ket River-is provided by Pokrovsky et al [8], who showed that climate warming in northern rivers may double or triple the concentration of DIC, Ca, Sr, U, but also increase the concentration of DOC, POC, and nutrients. The study applied a substituting-space-for-time approach for the south-north gradient of the studied river basins.…”
mentioning
confidence: 99%